Fission-track thermochronological evidence for the Yanshanian tectonic evolution of the northern Junggar Basin, northwest China - Li, Zhenhua; Chen, Zhanjun; Fan, Yuhai; Yu, Lan; Zhang, Suya; Li, Xiangyang (Frontiers in Earth Science, 2023)
The Junggar Basin is a multicycle intracontinental sedimentary basin developed on the pre-Mesozoic deformed basement. For a long time, the Junggar Basin and its adjacent Altai orogeny have been a focus of debate for geologists studying the opening and closing history of the Paleozoic Asian Ocean and Cenozoic intracontinental deformation. However, there has been no detailed research on the intracontinental tectonic activities of northern Xinjiang since the Mesozoic, particularly the Yanshanian tectonic activities in the northern Junggar Basin. Fission-track (FT) dating was conducted on 15 apatite samples and eight zircon samples obtained from the northern Junggar Basin to better understand the Yanshanian tectonic evolution. The results showed that apatite FT (AFT) ages ranged from 131 to 42 Ma and zircon FT ages ranged from 205 to 132 Ma. Based on the AFT track thermal history modeling and the regional geological data, we proposed that the northern Junggar Basin underwent three tectonic thermal events during 165–161, 93–81, and 72–66 Ma. The thermal events of 165–161 Ma may indicate magmatic activity during the Yanshanian, while the 93–86 and 72–66 Ma events reflect Late Cretaceous uplift and cooling. This study has confirmed the tectonic evolution of the Yanshanian in the northern Junggar Basin from the perspective of thermochronology. It has also revealed that the Yanshanian orogeny, a regional tectonic event, may have also occurred in northwest China.